Interspecies differences in the cytochrome P450 activity of hepatocytes exposed to PLGA and silica nanoparticles: an in vitro and in vivo investigation. Issue 11 (1st March 2018) - Cornu, Raphaël; Rougier, Nathalie; Pellequer, Yann; Lamprecht, Alf; Hamon, Paul; Li, Ruoya; Beduneau, Arnaud; Martin, Hélène
Abstract : This study emphasizes the interest to set up relevant in vitro models using human hepatic cells to evaluate the hepatotoxicity of nanomedicines. Abstract : Nanomedicines represent a promising approach in the treatment and diagnosis of numerous disorders. The majority of the injected dose of nanoparticles (NPs) is sequestrated in the liver. Despite this hepatic tropism, the interaction of NPs with the detoxification function of the liver remains unclear. The present study consists of evaluating the impact of biodegradable poly(lactide- co -glycolide) (PLGA) and silica NPs on cytochrome P450 (CYP) activities. The effects of NPs were evaluated in vitro on human and rat hepatocytes in primary cultures and in vivo by intravenous injections in healthy rats. More than the physicochemical properties, the composition of NPs (organic, inorganic) dramatically influenced the detoxification function of the liver. Silica NPs modulated the CYP activity both in rat and human hepatocytes, in contrast to PLGA NPs. A CYP isoform-dependent effect was reported and the modulation of the metabolic hepatic activity was species-dependent. Human hepatocytes were sensitive to an exposure to PLGA NPs, whereas no marked effect was detected in rat hepatocytes. The in vitro data obtained in rat hepatocytes were correlated with the in vivo data. This study emphasizes the interest to set up relevant in vitro models using human hepatic cells to evaluate the hepatotoxicity of nanomedicines.